The Labour Market and the Training of Librarians - de la Vega de Deza, Aurora (2005)
It refers to the future labour market of information professionals and its requirements, which allows us to reflect on the transformations that are taking place in this sense. Taking into account that librarianship is not a profession with a high unemployment rate, to meet the demands of a workforce with highly skilled job profiles, the need for permanent updating, both in the discipline itself and in related disciplines.